Feasibility and effectiveness of WhatsApp online group on breastfeeding by peer counsellors: a single-blinded, open-label pilot randomized controlled study - Heidi S. L. Fan; M. Y. Ho; Rachel W. T. Ko; Jojo Y. Y. Kwok; P. H. Chau; Janet Y. H. Wong; M. P. Wang; Kris Y. W. Lok (BMC, 2022)
Abstract Introduction With mobile technologies becoming more advanced and accessible, mobile health (mHealth) has been incorporated in delivering timely and convenient breastfeeding support. However, its feasibility and potential efficacy remain to be examined. Therefore, the primary objective of this study is to assess the feasibility and acceptability of an online instant messaging peer support group for breastfeeding. The secondary objective is to evaluate the effect of the intervention on breastfeeding outcomes. Methods A pilot randomized controlled trial was conducted. A total of 33 primiparous women were recruited in the antenatal clinic at a public hospital in Hong Kong between March and April 2021. They were randomized to receive either standard care (n = 18) or standard care and receive peer-group support in an online instant messaging app (n = 15). Participants received telephone follow-up for up to six months postpartum or until they stopped breastfeeding. After completing the study, six participants in the intervention group were interviewed to understand their perceptions of the intervention. Results This pilot study shows that online messaging peer support group is feasible and acceptable to women. In total, 54.4% of the eligible women agreed to participate, and 97.0% completed the follow-up. Participants perceived that providing peer support through instant messaging app is appropriate. It serves as a channel for the participants to ask questions and obtain information. Furthermore, meetings of the peer supporters and group members can be held to enhance the effectiveness of the intervention. In addition, no significant differences were found in any and exclusive breastfeeding rates, breastfeeding attitude, and breastfeeding self-efficacy between the two groups. Conclusions This study shows that online messaging peer support group is feasible and acceptable. A full-scale study should be conducted to understand the effect of the online instant messaging peer support group on breastfeeding outcomes. Trial Registration: The study protocol is registered on Clinicaltrial.gov (NCT04826796) on 1 April 2021